Information Retrieval Using a Middleware Approach. - Krstićev, Danijela Boberić (Information Technology & Libraries, 2013)
This paper explores the use of a mediator/wrapper approach to enable the search of an existing library management system using different information retrieval protocols. It proposes an architecture for a software component that will act as an intermediary between the library system and search services. It provides an overview of different approaches to add Z39.50 and Search/Retrieval via URL (SRU) functionality using a middleware approach that is implemented on the BISIS library management system. That wrapper performs transformation of Contextual Query Language (CQL) into Lucene query language. The primary aim of this software component is to enable search and retrieval of bibliographic records using the SRU and Z39.50 protocols, but the proposed architecture of the software components is also suitable for inclusion of the existing library management system into a library portal. The software component provides a single interface to server-side protocols for search and retrieval of records. Additional protocols could be used. This paper provides practical demonstration of interest to developers of library management systems and those who are trying to use open-source solutions to make their local catalog accessible to other systems.